How Middle School Curriculum in Chongqing Portrays Chinese Socialism - Peter Miller (University of Windsor, 2019)
This project is contextualized in Shijing Xu and Michael Connelly's (2013-2020) SSHRC Partnership Grant Project, Canada-China Reciprocal Learning in Teacher Education and School Education. The goal of the SSHRC Partnership Grant Project is to compare Canadian and Chinese education in such a way that the cultural narratives of each provide frameworks for understanding and appreciating educational similarities and differences (Xu & Connelly, 2017). The overall goal centers on reciprocal learning in teacher education between Canada and China. Xu and Connelly (2017) emphasize research that focuses on centering the voices of teachers in both Canada and China. This work seeks to help the project by providing data about China's politics curriculum to create a better understanding of China's education system, and to gain some insight into the hopes and dreams of Chinese politics teachers.